Prenatal diagnosis of partial monosomy 21q (21q22.1→qter) associated with intrauterine growth restriction and corpus callosum dysgenesis - Ying-Chung Chen; Wan-Ju Wu; Shun-Ping Chang; Gwo-Chin Ma; Ming Chen (Elsevier, 2020)
Objective: A prenatal diagnosis of partial monosomy 21q(21q22.1→ qter) in fetus with intrauterine growth restriction and corpus callosum dysgenesis but escaped from the detection by cell free DNA testing was reported. Case report: A 31-year-old, primigravida women, presented with intrauterine growth restriction and corpus callosum dysgenesis at 23 weeks of gestational age by anatomic ultrasound screening. The interphase fluorescence in situ hybridization (FISH) analysis on amniocytes revealed monosomy 21, while the cytogenetic analysis and array comparative genomic hybridization (CGH) with CytoScan gene chip ascertained a 12.35 Mb deletion at 21q22.1q22.3. Conclusion: Although noninvasive prenatal testing is used extensively and can be applied to certain microdeletion diseases, the application for uncommon deletion disorders such as the present case remains limited. Prenatal examination with detailed ultra-sonography combined with different modalities of invasive prenatal testing can provide a more comprehensive information. Keywords: Genetics, Down syndrome, Monosomy, Prenatal diagnosis, Single umbilical artery